Sistem Hambatan Berlapis Digitalisasi UMKM Kuliner: Studi Kualitatif Berbasis Kerangka TOE - Dafitri, Rahma; Daryani, Dian (Jurnal Bisnis dan Kewirausahaan, 2025)
Digital transformation barriers in culinary micro, small, and medium enterprises (MSMEs) form a layered barrier system that mutually reinforces and hinders optimization. This qualitative exploratory study involving 10 culinary MSMEs in Bandung identifies five main dimensions of barriers with 42 sub-categories analyzed using NVIVO. Digital literacy emerges as the dominant barrier, followed by technical, financial, operational, and external barriers. The study reveals three new theoretical findings: digital financial literacy as an overlooked dimension, time constraints creating repetitive cycles, and optimization paradox showing the phenomenon of "digital presence without digital performance". Barrier distribution varies based on MSME characteristics. Education-digital capability paradox shows bachelor's degree owners face the highest barriers. Middle-income digital trap appears in MSMEs with monthly revenue of Rp 5-8 million experiencing maximum technical complexity. Early-stage digital struggle dominates new MSMEs, while maturity advantage provides adaptation benefits for established MSMEs. The findings validate the Technology-Organization-Environment framework and generate a layered barrier system theory requiring comprehensive intervention approaches to break the mutually reinforcing barrier cycle.